ROMANIA'S CULTURAL PROFILE AND RECENT SOCIO-ECONOMIC CHANGES: IMPLICATIONS FOR PARENTAL BELIEFS AND PRACTICES - IONUȚ MONE; OANA BENGA (Studia Universitatis Babes-Bolyai, 2018)
ABSTRACT. In the present review our first aim is to analyze the Romanian culture and the way it is related to prevalent parental beliefs and practices. Our second aim is to explore how recent socio-economic changes that have taken place in the country are associated with changes in the Romanian culture and prevalent parental beliefs and practices. To this end, we will firstly analyze the Romanian culture starting from Hofstede's cultural dimensions. Afterwards, we will discuss the implications of this analysis for prevalent parental beliefs and practices. Next, we will review extant studies that focus on the Romanian culture, socio-economic changes and parental beliefs and practices, so as to see if they suggest that recent socio-economic changes are associated with the modification of the Romanian culture and prevalent parental beliefs and practices.